Integrating inquiry-based learning into the Academic Literacy course to enhance student learning - Nomakhaya Fidelia Mashiyi (University of Johannesburg, 2018)
In this paper, integrating inquiry-based learning (IBL) into an Academic Literacy (AL) course is examined in terms of student perceptions and experience. The study used a questionnaire to establish student perceptions and experiences of the intervention. The findings indicate that integration of IBL into Academic Literacy content could provide rich potential for promoting student engagement, and developing academic literacies, basic inquiry skills and higher-order skills. However, these benefits can only accrue if a programme-wide approach is adopted and there is collaboration between Academic Literacy lecturers and discipline experts. The findings also reveal that student identities, conceptions of learning, conceptualisations of AL, and the disciplinary context in which the IBL is incorporated into AL, all influence the success of the intervention. The study concludes that context is a key factor in the implementation of guided IBL at undergraduate level. Academic Literacy practitioners and subject specialists need to synergise their efforts and work collaboratively to achieve the learning objectives of guided IBL within AL. How to cite this article: MASHIYI, Nomakhaya. Integrating inquiry-based learning into the Academic Literacy course to enhance student learning. Scholarship of Teaching and Learning in the South v. 2, n. 2, p. 37-52, Sept. 2018. Available at: http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=33&path%5B%5D=32 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/